A bug’s life: diverse roles of insulin signaling in insect growth and development - Kelly E Dunham; Michelle L Bland (Current Opinion in Insect Science, 2026)

PFAS remediation in a bioelectrochemical system inoculated with the west branch consortium (WBC-2) - Haoran Yang; Michelle M. Lorah; Kelly S. Bender; Chunjie Xia; Jiasi Sun; Jia Liu (Journal of Water Process Engineering, 2026)

Late Aptian climate reconstruction based on palynological data from the Codó and Itapecuru formations, Parnaíba Basin, northeastern Brazil - Gabriel C. Correia; Marcelo de A. Carvalho; Michelle C.S. Giannerini; Natália de P. Sá; Kelly Cristine C.A. Bonito; Aristóteles M. Rios-Netto (Journal of South American Earth Sciences, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Intranasal vasopressin, but not oxytocin, decreases ethanol intake in socially housed mice - Michelle A. Nipper; Jonathan A. Zweig; Michael C. Johnson; Kelly M. Abshire; Andrey E. Ryabinin (Psychopharmacology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

The collective application of shorebird tracking data to conservation - Autumn‐Lynn Harrison; Candace Stenzel; Alexandra Anderson; Jessica Howell; Richard B. Lanctot; Marley Aikens; Joaquín Aldabe; Liam A. Berigan; Joël Bêty; Erik Blomberg; Juliana Bosi de Almeida; Andy J. Boyce; et al. (Conservation Biology, 2026)
Addressing urgent conservation issues, such as the drastic declines of North American migratory birds, requires creative, evidence‐based, efficient, and collaborative approaches. The abundance of over 50% of monitored North American shorebird populations has declined by over 50% since 1980. To address these declines, we developed a partnership of scientists and practitioners called the Shorebird Science and Conservation Collective (hereafter the collective ). The collective was founded to translate the combined findings of shorebird tracking data into on‐the‐ground conservation action. With advice from an advisory group, the collective acts as an intermediary whereby dedicated staff collate and analyze data contributions from scientists to support knowledge requests from conservation practitioners. In its first three years, data contributions from 75 organizations include over 7.1 million shorebird observations forming movement paths of 3420 individuals representing 36 species tracked across the Americas and have informed 18 conservation projects spanning education, land and species management, land conservation, and policy requests. Others engaged in translational science from big data could consider similar knowledge‐sharing models that prioritize usable data products, foster collaborative engagement between science experts and practitioners, build focused communities around topics or taxonomic groups, and employ a proof‐of‐concept phase to develop scalable solutions while making progress toward long‐term funding to sustain impact. As the volume of scientific data continues to grow, intermediaries, such as the collective, can be vital liaisons to rapidly integrate and interpret research to support conservation action. Dedicated to the memory of Shiloh Schulte and his conservation achievements for shorebirds.

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Angler Heterogeneity in Newfoundland and Labrador, Canada: Insights From Nearly Three Decades (1994–2022) of Atlantic Salmon Angler License and Activity Records - Travis E. Van Leeuwen; Michelle G. Fitzsimmons; J. Brian Dempson; Christopher W. White; Mark Young; Donald Keefe; Isabelle Schmelzer; Nicholas I. Kelly; Craig F. Purchase; Blair Adams; David Coté (Fisheries Management and Ecology, 2026)
Angler demographics and motivations are an important consideration to successful fisheries management. We examined 29 years of angler license and activity records from the recreational Atlantic salmon fishery in Newfoundland and Labrador, Canada to: (1) provide a contemporary evaluation of angler demographic trends; (2) evaluate age and regional differences between anglers who prioritized retention versus catch‐and‐release; and (3) discuss how various management and COVID restrictions affected angler participation and activity. Resident license holders made up 91.3% of total licenses purchased. The average age of license holders increased from 39 years of age in 1994 to 54 years of age in 2022, with 6–20 year olds making up

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Drivers of metabolism and decomposition in forested Lake Superior tributary streams - Renn C. Schipper; Michelle C. Kelly; Amy M. Marcarelli (Hydrobiologia, 2026)

From Revision to Practice: Key Changes in the Revised 2025 Scope and Standards of Practice for Registered Dietitian Nutritionists in Oncology Nutrition - Laura Kelly; Mridul Datta; Anna Arthur; Michelle Strang; Karen Hui (Journal of the Academy of Nutrition and Dietetics, 2025)

Deep-sea ecosystems of the North Atlantic Ocean: discovery, status, function and future challenges - A. Louise Allcock; Diva J. Amon; Amelia E.H. Bridges; Ana Colaço; Elva Escobar-Briones; Ana Hilário; Kerry L. Howell; Nélia C. Mestre; Frank E. Muller-Karger; Imants G. Priede; Paul V.R. Snelgrove; Kathleen Sullivan Sealey; et al. (Deep Sea Research Part I: Oceanographic Research Papers, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

Benthic community change and stress-tolerant coral at a high-latitude coral community in the northwestern Gulf of Mexico - Marissa F. Nuttall; Kelly O’Connell; Ryan J. Eckert; Emma L. Hickerson; Olivia Eisenbach; Donavon French; Jennifer L. DeBose; Michelle Johnston; G. P. Schmahl (Coral Reefs, 2025)

Having a gander at goose behaviour. Evaluating time-activity of captive and wild geese at two different wetland sites - Paul Rose; Amelia Roper; Christopher Giorgio; Joe Thomas; Robert Kelly; Michelle F. O’Brien (Applied Animal Behaviour Science, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Coral bleaching and mortality across a 24° latitudinal range in the Southwestern Atlantic during the fourth global bleaching event - Miguel Mies; Giovanna Destri; Carlos H. F. Lacerda; Júlia L. M. Carvalho; Júlia Y. Ibanhez; Arthur Z. Güth; André L. Luza; Luiza P. Campos; Aline C. Shimada; Kenzo N. T. Omaki; Bianca E. Jahn; Yasmim A. Abreu; et al. (Coral Reefs, 2025)

Exposure of free-ranging white-tailed deer (Odocoileus virginianus) to per- and polyfluoroalkyl substances (PFAS) at PFAS-impacted sites in Minnesota - Kelsie LaSharr; Deanna P. Scher; Summer Streets; Michelle Carstensen; Barbara Keller; James Kelly (Chemosphere, 2025)

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Remote sensing of electron precipitation mechanisms enabled by ELFIN mission operations and ADCS - Ethan Tsai; Akhil Palla; Austin Norris; James King; Cindy Russell; Sophie Ye; Jiashu Wu; Jason Mao; Sharvani Jha; Chanel Young; Graham Wing; Kevin Lian; et al. (Advances in Space Research, 2025)

TropiRoot 1.0: Database of tropical root characteristics across environments - Amanda L. Cordeiro; Daniela F. Cusack; Nathaly Guerrero‐Ramírez; Richard J. Norby; Laura Toro; Michelle Y. Wong; S. Joseph Wright; Kristine Grace M. Cabugao; Kelly M. Andersen; Lucia Fuchslueger; Colleen M. Iversen; Fiona Soper; et al. (Ecology, 2025)
Tropical ecosystems contain the world's largest biodiversity of vascular plants. Yet, our understanding of tropical functional diversity and its contribution to global diversity patterns is constrained by data availability. This discrepancy underscores an urgent need to bridge data gaps by incorporating comprehensive tropical root data into global datasets. Here, we provide a database of tropical root characteristics. This new database, TropiRoot 1.0, will be instrumental in evaluating an array of hypotheses pertaining to root functional ecology and plant biogeography, both within the tropics and relative to other global biomes. The data compilation was conducted by the TropiRoot Initiative, in partnership with the Fine‐Root Ecology Database (FRED) and the Global Root Trait (GRooT) database, Colorado State University (CSU) and the Smithsonian Tropical Research Institute (STRI). Literature search and data extraction were conducted between 2020 and 2024. Literature was identified using Web of Science, Scopus, and complemented using the expert knowledge of members of TropiRoot. To provide broad environmental and geographical distributions, literature searches included root characteristics (traits) across global change drivers, natural gradients, and from different continents. We adopted FRED standardized data columns and streamlined the format to enhance accessibility for data extraction across various user groups. This optimized framework resulted in a smaller, yet comprehensive datasheet. To make the database compatible with other global root trait initiatives, column identification was standardized following the codes provided by FRED. These efforts culminated in data extracted from 104 new sources, resulting in more than 8000 rows of data (either species or community data). Most of the data in TropiRoot 1.0 include root characteristics such as root biomass, morphology, root dynamics, mass fraction, architecture, anatomy, physiology, and root chemistry. This initiative represents a 30% increase in the currently available data for tropical roots in FRED. TropiRoot 1.0 contains root characteristics from 25 different countries, where seven are located in Asia, six in South America, five in Central America and the Caribbean, four in Africa, two in North America, and 1 in Oceania. Due to the volume of data, when ancillary data were available, including soil data, these data were either extracted and included in the database or its availability was recorded in an additional column. Multiple contributors checked the entries for outliers during the collation process to ensure data quality. For text‐based observations, we examined all cells to ensure that their content relates to their specific categories. For numerical observations, we ordered each numerical value from least to greatest and plotted the values, checking apparent outliers against the data in their respective sources and correcting or removing incorrect or impossible values. Some data (soil and aboveground) have different columns for the same variable presented in different units, including originally published units, but root characteristics data had units converted to match those reported in FRED. By filling a gap from global databases, TropiRoot 1.0 expands our knowledge of otherwise so far underrepresented regions and our ability to assess global trends. This advancement can be used to improve tropical forest representation in vegetation models. The data are freely available and should be cited when used.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Sponge species from New Zealand may transform and degrade dissolved organic matter - Tanja Stratmann; Mario L.M. Miranda; Anna de Kluijver; Kathrin Busch; Michelle Kelly; Sadie Mills; Peter J. Schupp (Journal of Experimental Marine Biology and Ecology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Aquatic ecosystem indices, linking ecosystem health to human health risks - Fanny G. De Carvalho; Adeline Loyau; Michelle Kelly-Irving; Dirk S. Schmeller (Biodiversity and Conservation, 2025)
The good functioning of aquatic ecosystems is essential for providing diverse ecosystem services that benefit humans. The degradation of ecosystem health due to continuous stressors, such as climate change or water pollution, is leading to an increase in human health risks and well-being. Indicators have been developed to determine human health risks from recreational and drinking water. Still, a general application to aquatic ecosystems linking ecosystem health and human health risks has not been done. We here reviewed indicators and indices applied to assess the health of aquatic ecosystems and their links with human health risk and well-being. We evaluated the extent to which indicators can witness a risk to human health and well-being. A total of 245 articles were reviewed, consisting of 185 on the assessment of aquatic ecosystem health and 60 linking ecosystem health and human health or well-being. Out of the 65 indices described, we evaluated the use of several parameters and their relevance to evaluate human health risks, including physico-chemical parameters, bioindicators, contaminants, and pathogens, therefore covering the various sources of ecosystem disturbance. Based on our assessment, we propose a set of indicators that would allow for the inclusion of risks for human health and well-being in the assessment of ecosystem health (e.g. coliforms, algae, pH, nutrients, chemical compounds, and ecosystem services). Measuring these parameters should be incorporated into future studies to allow an understanding of the linkage of ecosystem and human health.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Mixed contaminant exposure in tapwater and the potential implications for human-health in disadvantaged communities in California - Kelly L. Smalling; Kristin M. Romanok; Paul M. Bradley; Michelle L. Hladik; James L. Gray; Leslie K. Kanagy; R. Blaine McCleskey; Diana A. Stavreva; Annika K. Alexander-Ozinskas; Jesus Alonso; Wendy Avila; Sara E. Breitmeyer; et al. (Water Research, 2024)

Physical habitat is more than a sediment issue: A multi-dimensional habitat assessment indicates new approaches for river management - Matthew J. Cashman; Gina Lee; Leah E. Staub; Michelle P. Katoski; Kelly O. Maloney (Journal of Environmental Management, 2024)

Nutrient fluxes, oxygen consumption and fatty acid composition from deep-water demo- and hexactinellid sponges from New Zealand - Tanja Stratmann; Kathrin Busch; Anna de Kluijver; Michelle Kelly; Sadie Mills; Sven Rossel; Peter J. Schupp (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Temporal concentrations of Quaternary ammonium compounds in wastewater treatment effluents during the COVID-19 pandemic, 2020–2021 - Michelle L. Hladik; Michael S. Gross; Gabrielle P. Black; Dana W. Kolpin; Jason R. Masoner; Patrick J. Phillips; Paul M. Bradley; Kelly L. Smalling (Chemosphere, 2024)

Nexus among climate change, food systems, and human health: An interdisciplinary research framework in the Global South - Sávio Marcelino Gomes; Aline Martins Carvalho; Aníbal Silva Cantalice; Arthur Ramalho Magalhães; Daniel Tregidgo; Danilo Vicente Batista de Oliveira; Elenilma Barros da Silva; Elias Jacob de Menezes-Neto; Juliana Kelly da Silva Maia; Reginaldo Augusto Farias de Gusmão; Valdir de Moura Brito Júnior; Viviany Moura Chaves; et al. (Environmental Science & Policy, 2024)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Salmonids in hot water: An unprecedented warm‐water event in Labrador, a subarctic region of Canada - Emilie A. Geissinger; Travis E. Van Leeuwen; Nicholas Kelly; Curtis Pennell; Michelle G. Fitzsimmons; Steven Duffy; Rebecca Poole; Joey Angnatok; J. Brian Dempson; David Coté (Fisheries Management and Ecology, 2024)
Unprecedented warm river temperatures in July 2023 in Labrador, a subarctic region of Canada, were the highest since monitoring began (1994–2023) and ranged from 19.4°C (Hunt River) to 22.5°C (Eagle River). Incipient lethal water temperatures were exceeded for adult Atlantic salmon and brook trout (≥25°C) on 14 days in five of seven rivers and Arctic charr (≥24°C) on 17 days in six of seven rivers. Consequently, Labrador had the greatest number of angling restrictions and closures in 2023. Recent warming serves as a warning to fishery managers of regions historically unaffected by heat waves of the need to prepare action plans that mitigate the effects of a warming climate on fishes.

Peat profile database from peatlands in Canada - Ilka E. Bauer; Marissa A. Davies; Kelly A. Bona; Oleksandra Hararuk; Cindy H. Shaw; Daniel K. Thompson; Werner A. Kurz; Kara L. Webster; Michelle Garneau; Jim W. McLaughlin; Maara S. Packalen; Emily Prystupa; et al. (Ecology, 2024)
Peatlands cover approximately 12% of the Canadian landscape and play an important role in the carbon cycle through their centennial‐ to millennial‐scale storage of carbon under waterlogged and anoxic conditions. In recognizing the potential of these ecosystems as natural climate solutions and therefore the need to include them in national greenhouse gas inventories, the Canadian Model for Peatlands module (CaMP v. 2.0) was developed by the Canadian Forest Service. Model parameterization included compiling peat profiles across Canada to calibrate peat decomposition rates from different peatland types, to define typical bulk density profiles, and to describe the hydrological (i.e., water table) response of peatlands to climatic changes. A total of 1217 sites were included in the dataset from published and unpublished sources. The CORESITES table contains site location and summary data for each profile, as well as an estimate of total carbon mass per unit area (in megagrams of C per hectare). Total carbon mass per unit area at each location was calculated using bulk density and carbon content through each profile. The PROFILES table contains data for depth (in centimeters), bulk density (in grams per cubic meter), ash and carbon content (in percentage), and material descriptions for contiguous samples through each peat profile. Data gaps for bulk density and C content were filled using interpolation, regression trees, and assigned values based on material description and/or soil classification to allow for the estimation of total carbon mass per unit area. A subset of the sites ( N = 374) also have pH and pore water trace‐elemental geochemistry data and are found in the WATER table. The REFERENCES table contains the full citation of each source of the data and is linked to each core location through the SOURCEDATA table. The LOOKUP table defines codes in the database that required more space that what was sufficient in the metadata tables. The data can be accessed on Open Government Canada and will be useful for future work on carbon stock mapping and ecosystem modeling. All metadata and data are provided © Her Majesty the Queen in Right of Canada, 2023 and information contained in this publication may be reproduced for personal or public noncommercial purposes with attribution, whereas commercial reproduction and distribution are prohibited except with written permission from NRCan; complete details are noted in the Supporting Information file Metadata (see Class III.B.3: Copyright restrictions).

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

From field station to forecast: managing data at the Alaska Volcano Observatory - Michelle L. Coombs; Cheryl E. Cameron; Hannah R. Dietterich; Eleanor S. Boyce; Aaron G. Wech; Ronni Grapenthin; Kristi L. Wallace; Tom Parker; Taryn Lopez; Scott Crass; David Fee; Matthew M. Haney; et al. (Bulletin of Volcanology, 2024)

A Nourishing Space: Growing Client-Centered Health Professionals - Francilia Brito Silva; Samantha Honse; Miteshri Prajapati; Kathleen Davis; Marilyn Massey Stokes; Michelle Kelly; Kara Belt (Journal of Nutrition Education and Behavior, 2024)

Persisting neurobehavioral consequences of daily or intermittent paternal cannabis administration in F1 and F2 Rats - Andrew B. Hawkey; Sarabesh Natarajan; Olivia Kelly; Anas Gondal; Corinne Wells; Michelle Louise Jones; Amir H. Rezvani; Susan K. Murphy; Edward D. Levin (NeuroToxicology, 2024)

Tropical root responses to global changes: A synthesis - Daniela Yaffar; Laynara F. Lugli; Michelle Y. Wong; Richard J. Norby; Shalom D. Addo‐Danso; Marie Arnaud; Amanda L. Cordeiro; Lee H. Dietterich; Milton H. Diaz‐Toribio; Ming Y. Lee; Om Prakash Ghimire; Chris M. Smith‐Martin; et al. (Global Change Biology, 2024)
Tropical ecosystems face escalating global change. These shifts can disrupt tropical forests' carbon (C) balance and impact root dynamics. Since roots perform essential functions such as resource acquisition and tissue protection, root responses can inform about the strategies and vulnerabilities of ecosystems facing present and future global changes. However, root trait dynamics are poorly understood, especially in tropical ecosystems. We analyzed existing research on tropical root responses to key global change drivers: warming, drought, flooding, cyclones, nitrogen (N) deposition, elevated (e) CO 2 , and fires. Based on tree species‐ and community‐level literature, we obtained 266 root trait observations from 93 studies across 24 tropical countries. We found differences in the proportion of root responsiveness to global change among different global change drivers but not among root categories. In particular, we observed that tropical root systems responded to warming and eCO 2 by increasing root biomass in species‐scale studies. Drought increased the root: shoot ratio with no change in root biomass, indicating a decline in aboveground biomass. Despite N deposition being the most studied global change driver, it had some of the most variable effects on root characteristics, with few predictable responses. Episodic disturbances such as cyclones, fires, and flooding consistently resulted in a change in root trait expressions, with cyclones and fires increasing root production, potentially due to shifts in plant community and nutrient inputs, while flooding changed plant regulatory metabolisms due to low oxygen conditions. The data available to date clearly show that tropical forest root characteristics and dynamics are responding to global change, although in ways that are not always predictable. This synthesis indicates the need for replicated studies across root characteristics at species and community scales under different global change factors.

Simulation of soil temperature under maize: An inter-comparison among 33 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2024)

Revealing nitrate uptake and dispersion dynamics using high-frequency sensors and two-dimensional modeling in a large river system - Amirreza Zarnaghsh; Michelle Kelly; Amy Burgin; Admin Husic (Advances in Water Resources, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Community identified characteristics related to illegal dumping; a mixed methods study to inform prevention - Bernadette C. Hohl; Michelle C. Kondo; Laney A. Rupp; Richard C. Sadler; Catherine H. Gong; Kai Le; Melissa Hertlein; Christina Kelly; Marc A. Zimmerman (Journal of Environmental Management, 2023)

Monitoring population-level foraging distribution of a marine migratory species from land: strengths and weaknesses of the isotopic approach on the Northwest Atlantic loggerhead turtle aggregation - Simona A. Ceriani; Susan Murasko; David S. Addison; David Anderson; Greg Curry; Nicole A. Desjardin; Scott F. Eastman; Daniel R. Evans; Nancy Evou; Mariana M. P. B. Fuentes; Matthew H. Godfrey; Kristen M. Hart; et al. (Frontiers in Marine Science, 2023)
Assessing the linkage between breeding and non-breeding areas has important implications for understanding the fundamental biology of and conserving animal species. This is a challenging task for marine species, and in sea turtles a combination of stable isotope analysis (SIA) and satellite telemetry has been increasingly used. The Northwest Atlantic (NWA) loggerhead ( Caretta caretta ) Regional Management Unit, one of the largest sea turtle populations in the world, provides an excellent opportunity to investigate key biological patterns as well as methodological aspects related to the use of stable isotopes to infer spatial distribution of turtles in foraging areas. We provide the first comprehensive assessment of the annual distribution of NWA adult female loggerheads among foraging areas and investigate the efficacy of various analytical approaches as well as the effect of sample size in these types of studies. A total of 5168 individual females were sampled from seven Management Units (MUs) between 2013-2018. We provide the first estimate of the proportion of females originating from each MU that uses each foraging area and show how this proportion varies over time. We also estimate the relative importance (in terms of number of turtles) of each foraging area to the overall loggerhead breeding aggregation nesting in Florida and in the NWA for each year of the study. The foraging area used by reproductively active females differs considerably across MUs. One of these, the Subtropical NWA, is by far the most important foraging area in terms of both number of individuals and genetic diversity, and therefore this region may be considered as a conservation priority. Through simulations, we show that limited sizes of sample groups (unknowns; training; priors) may result in false geographic differentiation and consequently mislead interpretations. We provide thresholds and methodological recommendations for future studies. This study establishes a fundamental baseline for monitoring the annual contribution of foraging area to a terrestrial-based breeding aggregation of a marine animal in a cost-effective way. This type of monitoring allows for early detection of changes in foraging distributions—a possible effect of climate change on marine ecosystems or of area-specific anthropogenic threats.

Considerations for Water Temperature-Related Fishery Closures in Recreational Atlantic Salmon ( Salmo salar ) Catch and Release Fisheries: A Case Study from Eastern Canada - Travis E. Van Leeuwen; Sarah J. Lehnert; Cindy Breau; Michelle Fitzsimmons; Nicholas I. Kelly; J. Brian Dempson; Victoria M. Neville; Mark Young; Donald Keefe; Tomas J. Bird; David Cote (Reviews in Fisheries Science & Aquaculture, 2023)

Acanthamoeba castellanii trophozoites escape killing by neutrophil extracellular traps using their 3′-nucleotidase/nuclease activity - Luiz Fernando Carvalho-Kelly; Anita Leocadio Freitas-Mesquita; Michelle T.C. Nascimento; Claudia F. Dick; Eduarda de Souza-Maciel; Natalia C. Rochael; Elvira M. Saraiva; José Roberto Meyer-Fernandes (European Journal of Protistology, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

The E3 Ubiquitin Ligase SCF Cyclin F Promotes Sequestosome-1/p62 Insolubility and Foci Formation and is Dysregulated in ALS and FTD Pathogenesis - Jennilee M. Davidson; Sharlynn S. L. Wu; Stephanie L. Rayner; Flora Cheng; Kimberley Duncan; Carlo Russo; Michelle Newbery; Kunjie Ding; Natalie M. Scherer; Rachelle Balez; Alberto García-Redondo; Alberto Rábano; et al. (Molecular Neurobiology, 2023)
Amyotrophic lateral sclerosis (ALS)- and frontotemporal dementia (FTD)-linked mutations in CCNF have been shown to cause dysregulation to protein homeostasis. CCNF encodes for cyclin F, which is part of the cyclin F-E3 ligase complex SCF cyclinF known to ubiquitylate substrates for proteasomal degradation. In this study, we identified a function of cyclin F to regulate substrate solubility and show how cyclin F mechanistically underlies ALS and FTD disease pathogenesis. We demonstrated that ALS and FTD-associated protein sequestosome-1/p62 (p62) was a canonical substrate of cyclin F which was ubiquitylated by the SCF cyclinF complex. We found that SCF cyclin F ubiquitylated p62 at lysine(K)281, and that K281 regulated the propensity of p62 to aggregate. Further, cyclin F expression promoted the aggregation of p62 into the insoluble fraction, which corresponded to an increased number of p62 foci. Notably, ALS and FTD-linked mutant cyclin F p.S621G aberrantly ubiquitylated p62, dysregulated p62 solubility in neuronal-like cells, patient-derived fibroblasts and induced pluripotent stem cells and dysregulated p62 foci formation. Consistently, motor neurons from patient spinal cord tissue exhibited increased p62 ubiquitylation. We suggest that the p.S621G mutation impairs the functions of cyclin F to promote p62 foci formation and shift p62 into the insoluble fraction, which may be associated to aberrant mutant cyclin F-mediated ubiquitylation of p62. Given that p62 dysregulation is common across the ALS and FTD spectrum, our study provides insights into p62 regulation and demonstrates that ALS and FTD-linked cyclin F mutant p.S621G can drive p62 pathogenesis associated with ALS and FTD.

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Regional and time course differences in sweat cortisol, glucose, and select cytokine concentrations during exercise - Michelle A. King; Shyretha D. Brown; Kelly A. Barnes; Peter John D. De Chavez; Lindsay B. Baker (European Journal of Applied Physiology, 2023)
Introduction The use of sweat as a biofluid for non-invasive sampling and diagnostics is a popular area of research. However, concentrations of cortisol, glucose, and cytokines have not been described across anatomical regions or as time progresses throughout exercise. Purpose To determine regional and time course differences in sweat cortisol, glucose, and select cytokines (EGF, IFN-γ, IL-1β, IL-1α, IL-1ra, TNF-α, IL-6, IL-8, and IL-10). Methods Sweat was collected with absorbent patches from eight subjects (24–44 y; 80.2 ± 10.2 kg) on the forehead (FH), right dorsal forearm (RDF), right scapula (RS), and right triceps (RT) at 0–25 min, 30–55 min, and 60–85 min during 90 min of cycling (~ 82% HR max ) in a heated chamber (32 °C, 50% rh). ANOVA was used to determine the effect of site and time on outcomes. Data are reported as LS means ± SE. Results There was a significant effect of location on sweat analyte concentrations with FH having higher values than most other regions for cortisol (FH: 1.15 ± 0.08 ng/mL > RDF: 0.62 ± 0.09 ng/mL and RT: 0.65 ± 0.12 ng/mL, P = 0.02), IL-1ra ( P < 0.0001), and IL-8 ( P < 0.0001), but lower concentrations for glucose ( P = 0.01), IL-1α ( P < 0.0001), and IL-10 ( P = 0.02). Sweat IL-1β concentration was higher on the RS than RT ( P < 0.0001). Sweat cortisol concentration increased (25 min: 0.34 ± 0.10 ng/mL < 55 min: 0.89 ± 0.07 ng/mL < 85 min: 1.27 ± 0.07 ng/mL; P < 0.0001), while EGF ( P < 0.0001), IL-1ra ( P < 0.0001), and IL-6 ( P = 0.02) concentrations decreased over time. Conclusion Sweat analyte concentrations varied with time of sampling and anatomical region, which is essential information to consider when conducting future work in this area. Clinical trial identifier NCT04240951 registered January 27, 2020.

Evaluation of the Use of Diluted Formic Acid in Sample Preparation for Elemental Determination in Crustacean Samples by MIP OES - Michelle S. Lemos; Kelly G. Fernandes Dantas (Biological Trace Element Research, 2023)

A retrospective cohort study of genetic referral and diagnosis of Lynch syndrome in patients with cutaneous sebaceous lesions - Meera Kattapuram; Christina Shabet; Sarah Austin; Michelle F. Jacobs; Erika Koeppe; Emily H. Smith; Lori Lowe; Tobias Else; Kelly B. Cha (Familial Cancer, 2023)

Ovarian follicle dynamics in ewes treated with intra-vaginal progesterone pessaries. 2. Factors affecting timing of estrus and reproductive outcomes following artificial insemination - Simon K. Walker; Jennifer M. Kelly; Michelle L. Hebart; Alyce M.S. Swinbourne; Alice C. Weaver; David O. Kleemann (Theriogenology, 2023)

Juxtaposition of intensive agriculture, vulnerable aquifers, and mixed chemical/microbial exposures in private-well tapwater in northeast Iowa - Paul M. Bradley; Dana W. Kolpin; Darrin A. Thompson; Kristin M. Romanok; Kelly L. Smalling; Sara E. Breitmeyer; Mary C. Cardon; David M. Cwiertny; Nicola Evans; R. William Field; Michael J. Focazio; Laura E. Beane Freeman; et al. (Science of The Total Environment, 2023)

Simulation of evapotranspiration and yield of maize: An inter-comparison among 41 maize models - Bruce A. Kimball; Kelly R. Thorp; Kenneth J. Boote; Claudio Stockle; Andrew E. Suyker; Steven R. Evett; David K. Brauer; Gwen G. Coyle; Karen S. Copeland; Gary W. Marek; Paul D. Colaizzi; Marco Acutis; et al. (Agricultural and Forest Meteorology, 2023)

Vulnerability to climate change of managed stocks in the California Current large marine ecosystem - Michelle M. McClure; Melissa A. Haltuch; Ellen Willis-Norton; David D. Huff; Elliott L. Hazen; Lisa G. Crozier; Michael G. Jacox; Mark W. Nelson; Kelly S. Andrews; Lewis A.K. Barnett; Aaron M. Berger; Sabrina Beyer; et al. (Frontiers in Marine Science, 2023)
Introduction Understanding how abundance, productivity and distribution of individual species may respond to climate change is a critical first step towards anticipating alterations in marine ecosystem structure and function, as well as developing strategies to adapt to the full range of potential changes. Methods This study applies the NOAA (National Oceanic and Atmospheric Administration) Fisheries Climate Vulnerability Assessment method to 64 federally-managed species in the California Current Large Marine Ecosystem to assess their vulnerability to climate change, where vulnerability is a function of a species’ exposure to environmental change and its biological sensitivity to a set of environmental conditions, which includes components of its resiliency and adaptive capacity to respond to these new conditions. Results Overall, two-thirds of the species were judged to have Moderate or greater vulnerability to climate change, and only one species was anticipated to have a positive response. Species classified as Highly or Very Highly vulnerable share one or more characteristics including: 1) having complex life histories that utilize a wide range of freshwater and marine habitats; 2) having habitat specialization, particularly for areas that are likely to experience increased hypoxia; 3) having long lifespans and low population growth rates; and/or 4) being of high commercial value combined with impacts from non-climate stressors such as anthropogenic habitat degradation. Species with Low or Moderate vulnerability are either habitat generalists, occupy deep-water habitats or are highly mobile and likely to shift their ranges. Discussion As climate-related changes intensify, this work provides key information for both scientists and managers as they address the long-term sustainability of fisheries in the region. This information can inform near-term advice for prioritizing species-level data collection and research on climate impacts, help managers to determine when and where a precautionary approach might be warranted, in harvest or other management decisions, and help identify habitats or life history stages that might be especially effective to protect or restore.

Coral disease outbreak at the remote Flower Garden Banks, Gulf of Mexico - Michelle A. Johnston; Michael S. Studivan; Ian C. Enochs; Adrienne M. S. Correa; Nicole Besemer; Ryan J. Eckert; Kimberly Edwards; Ryan Hannum; Xinping Hu; Marissa Nuttall; Kelly O’Connell; Ana M. Palacio-Castro; et al. (Frontiers in Marine Science, 2023)
East and West Flower Garden Bank (FGB) are part of Flower Garden Banks National Marine Sanctuary (FGBNMS) in the northwest Gulf of Mexico. This geographically-isolated reef system contains extensive coral communities with the highest coral cover (>50%) in the continental United States due, in part, to their remoteness and depth, and have historically exhibited low incidence of coral disease and bleaching despite ocean warming. Yet in late August 2022, disease-like lesions on seven coral species were reported during routine monitoring surveys on East and West FGB (2.1–2.6% prevalence). A series of rapid response cruises were conducted in September and October 2022 focused on 1) characterizing signs and epidemiological aspects of the disease across FGB and within long-term monitoring sites, 2) treating affected coral colonies with Base 2B plus amoxicillin, and 3) collecting baseline images through photostations and photomosaics. Marginal and/or multi-focal lesions and tissue loss were observed, often associated with substantial fish and invertebrate predation, affecting the dominant coral species Pseudodiploria strigosa (7–8% lesion prevalence), Colpophyllia natans (11–18%), and Orbicella spp. (1%). Characterizing this disease event during its early epidemic phase at East and West FGB provides a critical opportunity to observe how coral disease functions in a relatively healthy coral ecosystem versus on reefs chronically affected by various stressors (e.g., Caribbean reefs adjacent to urban centers). Insights into the etiology, spread, and impacts of the disease can ultimately inform efforts to mitigate its effects on coral communities.

Characterizing the Biological Community before and after Partial Removal of an Offshore Gas Platform in the Northwestern Gulf of Mexico - Michelle A. Johnston; Marissa F. Nuttall; Emma L. Hickerson; Kelly O’Connell; Raven D. Blakeway; John A. Embesi; Jimmy MacMillan; Douglas Peter; George P. Schmahl (Environmental Management, 2022)

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Transmission of Klebsiella strains and plasmids within and between grey‐headed flying fox colonies - Ben Vezina; Louise M. Judd; Fiona K. McDougall; Wayne S. J. Boardman; Michelle L. Power; Jane Hawkey; Sylvain Brisse; Jonathan M. Monk; Kathryn E. Holt; Kelly L. Wyres (Environmental Microbiology, 2022)
Summary The grey‐headed flying fox ( Pteropus poliocephalus ) is an endemic Australian fruit bat, known to carry zoonotic pathogens. We recently showed they harbour bacterial pathogen Klebsiella pneumoniae and closely related species in the K . pneumoniae species complex ( Kp SC); however, the dynamics of Kp SC transmission and gene flow within flying fox colonies are poorly understood. High‐resolution genome comparisons of 39 Kp SC isolates from grey‐headed flying foxes identified five putative strain transmission clusters (four intra‐ and one inter‐colony). The instance of inter‐colony strain transmission of K . africana was found between two flying fox populations within flying distance, indicating either direct or indirect transmission through a common food/water source. All 11 plasmids identified within the Kp SC isolates showed 73% coverage (mean) and ≥95% identity to human‐associated Kp SC plasmids, indicating gene flow between human clinical and grey‐headed flying fox isolates. Along with strain transmission, inter‐species horizontal plasmid transmission between K . pneumoniae and Klebsiella africana was also identified within a flying fox colony. Finally, genome‐scale metabolic models were generated to predict and compare substrate usage to previously published Kp SC models, from human and environmental sources. These models indicated no distinction on the basis of metabolic capabilities. Instead, metabolic capabilities were consistent with population structure and ST/lineage.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Considering Fish as Recipients of Ecosystem Services Provides a Framework to Formally Link Baseline, Development, and Post-operational Monitoring Programs and Improve Aquatic Impact Assessments for Large Scale Developments - Carolyn J. M. Brown; R. Allen Curry; Michelle A. Gray; Jennifer Lento; Deborah L. MacLatchy; Wendy A. Monk; Scott A. Pavey; André St-Hilaire; Bernhard Wegscheider; Kelly R. Munkittrick (Environmental Management, 2022)
In most countries, major development projects must satisfy an Environmental Impact Assessment (EIA) process that considers positive and negative aspects to determine if it meets environmental standards and appropriately mitigates or offsets negative impacts on the values being considered. The benefits of before-after-control-impact monitoring designs have been widely known for more than 30 years, but most development assessments fail to effectively link pre- and post-development monitoring in a meaningful way. Fish are a common component of EIA evaluation for both socioeconomic and scientific reasons. The Ecosystem Services (ES) concept was developed to describe the ecosystem attributes that benefit humans, and it offers the opportunity to develop a framework for EIA that is centred around the needs of and benefits from fish. Focusing an environmental monitoring framework on the critical needs of fish could serve to better align risk, development, and monitoring assessment processes. We define the ES that fish provide in the context of two common ES frameworks. To allow for linkages between environmental assessment and the ES concept, we describe critical ecosystem functions from a fish perspective to highlight potential monitoring targets that relate to fish abundance, diversity, health, and habitat. Finally, we suggest how this framing of a monitoring process can be used to better align aquatic monitoring programs across pre-development, development, and post-operational monitoring programs.

Cancer disparities in the context of rurality: risk factors and screening across various U.S. rural classification codes - Kelly A. Hirko; Huiwen Xu; Laura Q. Rogers; Michelle Y. Martin; Siddhartha Roy; Kimberly M. Kelly; Shannon M. Christy; Kimlin Tam Ashing; Jean C. Yi; Marquita W. Lewis-Thames; Cathy D. Meade; Qian Lu; et al. (Cancer Causes & Control, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Using Decision Analysis to Integrate Habitat and Community Values for Coastal Resilience Planning - David M. Martin; Jackie A. Specht; Michelle R. Canick; Kelly L. Leo; Kathleen Freeman (Estuaries and Coasts, 2022)
Decision analysis is applied to habitat and community resilience planning in Maryland, USA. Sea level rise is causing wetland loss and increased flooding in coastal areas. A team at The Nature Conservancy analyzed a decision to identify high-value conservation planning units across Maryland’s Lower Eastern Shore. The team selected two fundamental objectives: minimize habitat loss and minimize community flood impacts. Sub-objectives included habitat function, habitat migration potential, critical infrastructure, and social vulnerability. Spatial attributes were selected based on ecological knowledge about habitat and socio-economic knowledge about sustaining populations in flood-prone areas. Seven planning units were developed across the Lower Eastern Shore. Single-attribute value functions determined the overall value of each unit per attribute, whereas multi-attribute value functions determined the overall value of each unit for all fundamental objectives. Sensitivity analysis incorporated data adjustments based on different flood scenarios and unit sizes, and variation in attribute weights associated with the multi-attribute value function. The Pareto efficiency principle revealed tradeoffs between units for habitat protection and management and community engagement and adaptation. Results indicate that four units are Pareto efficient under different sensitivity iterations and they trade off value in the fundamental objectives, whereas one unit provides the highest combined habitat and community value. This research guided thinking about equity in decision making and targeting conservation actions at local scales. The approach and methods can be used to inform conservation decisions in other similar contexts.

MYT1L-associated neurodevelopmental disorder: description of 40 new cases and literature review of clinical and molecular aspects - Juliette Coursimault; Anne-Marie Guerrot; Michelle M. Morrow; Catherine Schramm; Francisca Millan Zamora; Anita Shanmugham; Shuxi Liu; Fanggeng Zou; Frédéric Bilan; Gwenaël Le Guyader; Ange-Line Bruel; Anne-Sophie Denommé-Pichon; et al. (Human Genetics, 2022)

Using Global-Scale Earth System Models for Regional Fisheries Applications - Kelly A. Kearney; Steven J. Bograd; Elizabeth Drenkard; Fabian A. Gomez; Melissa Haltuch; Albert J. Hermann; Michael G. Jacox; Isaac C. Kaplan; Stefan Koenigstein; Jessica Y. Luo; Michelle Masi; Barbara Muhling; et al. (Frontiers in Marine Science, 2021)
Climate change may impact ocean ecosystems through a number of mechanisms, including shifts in primary productivity or plankton community structure, ocean acidification, and deoxygenation. These processes can be simulated with global Earth system models (ESMs), which are increasingly being used in the context of fisheries management and other living marine resource (LMR) applications. However, projections of LMR-relevant metrics such as net primary production can vary widely between ESMs, even under identical climate scenarios. Therefore, the use of ESM should be accompanied by an understanding of the structural differences in the biogeochemical sub-models within ESMs that may give rise to these differences. This review article provides a brief overview of some of the most prominent differences among the most recent generation of ESM and how they are relevant to LMR application.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Interactions Between Ultraviolet B Radiation, Warming, and Changing Nitrogen Source May Reduce the Accumulation of Toxic Pseudo-nitzschia multiseries Biomass in Future Coastal Oceans - Kyla J. Kelly; Fei-Xue Fu; Xiaowen Jiang; He Li; Dong Xu; Nina Yang; Michelle A. DeMers; Joshua D. Kling; Kunshan Gao; Naihao Ye; David A. Hutchins (Frontiers in Marine Science, 2021)
Understanding the environmental conditions that trigger Pseudo-nitzschia bloom formation and domoic acid (DA) production is critical as the frequency and severity of these toxic blooms increases in the face of anthropogenic change. However, predicting the formation of these harmful blooms in a future ocean remains a challenge. Previous studies have examined the effects of single environmental drivers on Pseudo-nitzschia spp. growth and toxin production, but few have considered the interactions between them. In this multiple driver study with Pseudo-nitzschia multiseries , we used a full factorial matrix experimental design to examine the simultaneous effects of temperature (20 and 25°C), nitrogen source (nitrate and urea), and irradiance (photosynthetically active radiation with and without ultraviolet B radiation; UVB). This strain of P. multiseries was unable to withstand prolonged exposures (>0.5 h) to 0.06 mw⋅cm –2 UVB light, with implications for near-surface bloom formation if future shallower mixed layers increase UVB exposure. Growth rates were inhibited by UVB, but photosynthesis and carbon fixation continued at a reduced capacity. Additionally, DA synthesis continued despite UVB-induced growth inhibition. Warming by 5°C enhanced cellular DA quotas three-fold. Within these warmer treatments, urea-grown cultures exposed to UVB had the highest amount of DA per cell, suggesting that interactive effects between UVB exposure, warming, and urea can synergistically enhance toxin production. However, overall production of toxic biomass was low, as growth-integrated DA production rates were near zero. This indicates that although Pseudo-nitzschia multiseries cell-specific toxicity could worsen in an anthropogenically-altered future ocean, bloom formation may be inhibited by increased exposure to UVB. This multi-variable experimental approach revealed previously unknown interactions that could not have been predicted based on combined effects of single-variable experiments. Although P. multiseries DA production may be enhanced in a future ocean, inherent sensitivity to prolonged UVB exposure may moderate trophic transfer of toxin to coastal food webs.

Recognize fish as food in policy discourse and development funding - Abigail Bennett; Xavier Basurto; John Virdin; Xinyan Lin; Samantha J. Betances; Martin D. Smith; Edward H. Allison; Barbara A. Best; Kelly D. Brownell; Lisa M. Campbell; Christopher D. Golden; Elizabeth Havice; et al. (Ambio, 2021)
The international development community is off-track from meeting targets for alleviating global malnutrition. Meanwhile, there is growing consensus across scientific disciplines that fish plays a crucial role in food and nutrition security. However, this ‘fish as food’ perspective has yet to translate into policy and development funding priorities. We argue that the traditional framing of fish as a natural resource emphasizes economic development and biodiversity conservation objectives, whereas situating fish within a food systems perspective can lead to innovative policies and investments that promote nutrition-sensitive and socially equitable capture fisheries and aquaculture. This paper highlights four pillars of research needs and policy directions toward this end. Ultimately, recognizing and working to enhance the role of fish in alleviating hunger and malnutrition can provide an additional long-term development incentive, beyond revenue generation and biodiversity conservation, for governments, international development organizations, and society more broadly to invest in the sustainability of capture fisheries and aquaculture.

Correlates of bird collisions with buildings across three North American countries - Jared A. Elmore; Stephen B. Hager; Bradley J. Cosentino; Timothy J. O'Connell; Corey S. Riding; Michelle L. Anderson; Marja H. Bakermans; Than J. Boves; David Brandes; Eric M. Butler; Michael W. Butler; Nicolette L. Cagle; et al. (Conservation Biology, 2021)
Collisions with buildings cause up to 1 billion bird fatalities annually in the United States and Canada. However, efforts to reduce collisions would benefit from studies conducted at large spatial scales across multiple study sites with standardized methods and consideration of species‐ and life‐history‐related variation and correlates of collisions. We addressed these research needs through coordinated collection of data on bird collisions with buildings at sites in the United States (35), Canada (3), and Mexico (2). We collected all carcasses and identified species. After removing records for unidentified carcasses, species lacking distribution‐wide population estimates, and species with distributions overlapping fewer than 10 sites, we retained 269 carcasses of 64 species for analysis. We estimated collision vulnerability for 40 bird species with ≥2 fatalities based on their North American population abundance, distribution overlap in study sites, and sampling effort. Of 10 species we identified as most vulnerable to collisions, some have been identified previously (e.g., Black‐throated Blue Warbler [ Setophaga caerulescens ]), whereas others emerged for the first time (e.g., White‐breasted Nuthatch [ Sitta carolinensis ]), possibly because we used a more standardized sampling approach than past studies. Building size and glass area were positively associated with number of collisions for 5 of 8 species with enough observations to analyze independently. Vegetation around buildings influenced collisions for only 1 of those 8 species (Swainson's Thrush [ Catharus ustulatus ]). Life history predicted collisions; numbers of collisions were greatest for migratory, insectivorous, and woodland‐inhabiting species. Our results provide new insight into the species most vulnerable to building collisions, making them potentially in greatest need of conservation attention to reduce collisions and into species‐ and life‐history‐related variation and correlates of building collisions, information that can help refine collision management.

A scoping review of drought impacts on health and society in North America - Margaret Sugg; Jennifer Runkle; Ronnie Leeper; Hannah Bagli; Andrew Golden; Leah Hart Handwerger; Tatiana Magee; Camila Moreno; Rhiannon Reed-Kelly; Michelle Taylor; Sarah Woolard (Climatic Change, 2020)

Monanchocidin A From Subarctic Sponges of the Genus Monanchora and Their Promising Selectivity Against Melanoma in vitro - Vedanjali Gogineni; Joonseok Oh; Amanda L. Waters; Michelle Kelly; Robert Stone; Mark T. Hamann (Frontiers in Marine Science, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Microwave-Assisted Digestion Procedures Using Diluted Oxidant Mixture for Elemental Analysis of Crustaceans by MIP OES - Michelle S. Lemos; Allan S. Cruz; Kelly G. Fernandes Dantas (Biological Trace Element Research, 2019)

Microbiota Alterations in Alzheimer’s Disease: Involvement of the Kynurenine Pathway and Inflammation - Michelle L. Garcez; Kelly R. Jacobs; Gilles J. Guillemin (Neurotoxicity Research, 2019)

The Relationship Between Circulating Acetaminophen-Protein Adduct Concentrations and Alanine Aminotransferase Activities in Patients With and Without Acetaminophen Overdose and Toxicity - Steven C. Curry; Angela Padilla-Jones; Anne-Michelle Ruha; Ayrn D. O’Connor; A Min Kang; Diana G. Wilkins; Hartmut Jaeschke; Kelly Wilhelms; Richard D. Gerkin (Journal of Medical Toxicology, 2019)

The Virtual Toxicology Journal Club: the Dissemination and Discussion of Noteworthy Manuscripts Using Twitter - Peter R. Chai; Anne-Michelle Ruha; Kelly E. Wong; Derek L. Monette; Meghan B. Spyres; Jeff Lapoint; Howard Greller; Mark B. Mycyk (Journal of Medical Toxicology, 2018)

Development and characterization of ten highly polymorphic microsatellite markers for the demosponge Poecillastra laminaris (Sollas) - Cong Zeng; Michelle Kelly; Jonathan P. A. Gardner (Marine Biodiversity, 2018)

Using niche breadth theory to explain generalization in mutualisms - Rebecca T. Batstone; Kelly A. Carscadden; Michelle E. Afkhami; Megan E. Frederickson (Ecology, 2018)
For a mutualism to remain evolutionarily stable, theory predicts that mutualists should limit their associations to high‐quality partners. However, most mutualists either simultaneously or sequentially associate with multiple partners that confer the same type of reward. By viewing mutualisms through the lens of niche breadth evolution, we outline how the environment shapes partner availability and relative quality, and ultimately a focal mutualist's partner breadth. We argue that mutualists that associate with multiple partners may have a selective advantage compared to specialists for many reasons, including sampling, complementarity, and portfolio effects, as well as the possibility that broad partner breadth increases breadth along other niche axes. Furthermore, selection for narrow partner breadth is unlikely to be strong when the environment erodes variation in partner quality, reduces the costs of interacting with low‐quality partners, spatially structures partner communities, or decreases the strength of mutualism. Thus, we should not be surprised that most mutualists have broad partner breadth, even if it allows for ineffective partners to persist.

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Genetic structure of the beaked whale genus Berardius in the North Pacific, with genetic evidence for a new species - Phillip A. Morin; C. Scott Baker; Reid S. Brewer; Alexander M. Burdin; Merel L. Dalebout; James P. Dines; Ivan Fedutin; Olga Filatova; Erich Hoyt; Jean‐Luc Jung; Morgane Lauf; Charles W. Potter; et al. (Marine Mammal Science, 2017)
There are two recognized species in the genus Berardius , Baird's and Arnoux's beaked whales. In Japan, whalers have traditionally recognized two forms of Baird's beaked whales, the common “slate‐gray” form and a smaller, rare “black” form. Previous comparison of mt DNA control region sequences from three black specimens to gray specimens around Japan indicated that the two forms comprise different stocks and potentially different species. We have expanded sampling to include control region haplotypes of 178 Baird's beaked whales from across their range in the North Pacific. We identified five additional specimens of the black form from the Aleutian Islands and Bering Sea, for a total of eight “black” specimens. The divergence between mt DNA haplotypes of the black and gray forms of Baird's beaked whale was greater than their divergence from the congeneric Arnoux's beaked whale found in the Southern Ocean, and similar to that observed among other congeneric beaked whale species. Taken together, genetic evidence from specimens in Japan and across the North Pacific, combined with evidence of smaller adult body size, indicate presence of an unnamed species of Berardius in the North Pacific.

An analysis of the sponge Acanthostrongylophora igens' microbiome yields an actinomycete that produces the natural product manzamine A - Amanda L. Waters; Olivier Peraud; Noer Kasanah; James W. Sims; Nuwan Kothalawala; Matthew A. Anderson; Samuel H. Abbas; Karumanchi V. Rao; Vijay R. Jupally; Michelle Kelly; Amala Dass; Russell T. Hill; et al. (Frontiers in Marine Science, 2014)

The gravity of pollination: integrating at‐site features into spatial analysis of contemporary pollen movement - Michelle F. DiLeo; Jenna C. Siu; Matthew K. Rhodes; Adriana López‐Villalobos; Angela Redwine; Kelly Ksiazek; Rodney J. Dyer (Molecular Ecology, 2014)
Pollen‐mediated gene flow is a major driver of spatial genetic structure in plant populations. Both individual plant characteristics and site‐specific features of the landscape can modify the perceived attractiveness of plants to their pollinators and thus play an important role in shaping spatial genetic variation. Most studies of landscape‐level genetic connectivity in plants have focused on the effects of interindividual distance using spatial and increasingly ecological separation, yet have not incorporated individual plant characteristics or other at‐site ecological variables. Using spatially explicit simulations, we first tested the extent to which the inclusion of at‐site variables influencing local pollination success improved the statistical characterization of genetic connectivity based upon examination of pollen pool genetic structure. The addition of at‐site characteristics provided better models than those that only considered interindividual spatial distance (e.g. IBD ). Models parameterized using conditional genetic covariance (e.g. population graphs) also outperformed those assuming panmixia. In a natural population of Cornus florida L. (Cornaceae), we showed that the addition of at‐site characteristics (clumping of primary canopy opening above each maternal tree and maternal tree floral output) provided significantly better models describing gene flow than models including only between‐site spatial ( IBD ) and ecological (isolation by resistance) variables. Overall, our results show that including interindividual and local ecological variation greatly aids in characterizing landscape‐level measures of contemporary gene flow.

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Characteristics and determinants of human-carnivore conflict in South African farmland - Michelle Thorn; Matthew Green; Dawn Scott; Kelly Marnewick (Biodiversity and Conservation, 2013)

Implications for cancer genetics practice of pro-actively assessing family history in a General Practice cohort in North West London - Kelly Kohut; Lucia D’Mello; Elizabeth K. Bancroft; Sarah Thomas; Mary-Anne Young; Kathryn Myhill; Susan Shanley; Brian H. J. Briggs; Michelle Newman; Ifthikhar M. Saraf; Penny Cox; Sarah Scambler; et al. (Familial Cancer, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Cadmium stress: an oxidative challenge - Ann Cuypers; Michelle Plusquin; Tony Remans; Marijke Jozefczak; Els Keunen; Heidi Gielen; Kelly Opdenakker; Ambily Ravindran Nair; Elke Munters; Tom J. Artois; Tim Nawrot; Jaco Vangronsveld; et al. (BioMetals, 2010)

A novel D-ring unsaturated A-nor sterol from the Indonesian sponge, Axinella carteri Dendy - Winklet A. Gallimore; Chelsea Cabral; Michelle Kelly; Paul J. Scheuer (Natural Product Research, 2008)

Estimation of the distribution of intramuscular current during electrical stimulation of the quadriceps muscle - Jerrold Petrofsky; Michelle Prowse; Melanie Bain; Elaine Ebilane; Hye Jin Suh; Jennifer Batt; Daryl Lawson; Viviana Hernandez; Armia Abdo; Tien-ning Yang; Enrique Mendoza; Kelly Collins; et al. (European Journal of Applied Physiology, 2008)

Geographic patterns of introgressive hybridization between native Yellowstone cutthroat trout (Oncorhynchus clarkii bouvieri) and introduced rainbow trout (O. mykiss) in the South Fork of the Snake River watershed, Idaho - Kelly Gunnell; Michelle K. Tada; Felicia A. Hawthorne; Ernest R. Keeley; Margaret B. Ptacek (Conservation Genetics, 2008)

A Multi-residue Method for the Analysis of Pesticides and Pesticide Degradates in Water Using HLB Solid-phase Extraction and Gas Chromatography–Ion Trap Mass Spectrometry - Michelle L. Hladik; Kelly L. Smalling; Kathryn M. Kuivila (Bulletin of Environmental Contamination and Toxicology, 2008)

Relevance of BAC transgene copy number in mice: transgene copy number variation across multiple transgenic lines and correlations with transgene integrity and expression - Kelly J. Chandler; Ronald L. Chandler; Eva M. Broeckelmann; Yue Hou; E. Michelle Southard-Smith; Douglas P. Mortlock (Mammalian Genome, 2007)

Silica banding in the deep‐sea lithistid sponge Corallistes undulatus : Investigating the potential influence of diet and environment on growth - Michael J. Ellwood; Michelle Kelly; Bertrand Richer de Forges (Limnology and Oceanography, 2007)
We present detailed records of trace metals and carbon isotopes to understand siliceous spicule formation in the deep‐sea lithistid sponge Corallistes undulatus Levi and Levi, 1983 (Demospongiae: Corallistidae). X‐ray analysis of two longitudinal sections removed from the lamellae of the cup‐shaped sponge revealed 144 and 137 light and dark density band‐pairs, respectively, within the siliceous skeleton. Four portions of silica were removed along one of the sections for silicon‐32 ( 32 Si) dating in order to constrain the overall extension rate of the sponge. Although there was some variability in the 32 Si data, the overall age established using these data indicated that the sponge was between 135 and 160 yr old. This agreed well with the counts of density band‐pairs, indicating that these band‐pairs represent an annual deposition of layers of silica in the desma skeleton. Links between silica deposition and growth (food supply) were established using the Δ 14 carbon (C) and Δ 13 C signatures of organic material trapped with the spicule matrix and the zinc content of the silica. A carbon budget based on these results indicated that the amount of fresh, labile surface export organic carbon reaching C. undulatus was not sufficient to support its growth. The Δ 14 C results for organic carbon trapped in the silica desmas, deposited after the 1960s, supports this assertion; only a small atmospheric nuclear weapons ‚bomb’ spike was observed in the Δ 14 C data. Taken together, the Δ 14 C, Δ 13 C, and trace‐metal results all indicate that the organic carbon source to C. undulatus is likely to be a mixture of fresh, labile, surface‐derived material and older, perhaps sediment‐derived material, with the latter being dominant.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Zebra Mussel Antifouling Activity of the Marine Natural Product Aaptamine and Analogs - Jeffrey A. Diers; John J. Bowling; Stephen O. Duke; Subagus Wahyuono; Michelle Kelly; Mark T. Hamann (Marine Biotechnology, 2006)

An early Paleogene sponge fauna, Chatham Island, New Zealand - Michelle Kelly; John S. Buckeridge (New Zealand Journal of Marine and Freshwater Research, 2005)
A late Paleocene‐early Eocene (c. 60–53 Ma) poriferan fauna, comprising hexactinellids (Class Hexactinellida), astrophorids (Class Demospongiae: Family Astrophorida), and lithistids (“lithistid” Demospongiae) has been identified from the Tutuiri Greensand outcropping on the north coast of Chatham Island, New Zealand. Most of the fossils are hexactinellids, comprising extremely delicate siliceous networks embedded in friable sandstone. The sediment matrix within and around these skeletons contains numerous siliceous demosponge spicules, many of which are exceptionally well preserved. The soft friable matrix of the Tutuiri Greensand has made extraction a relatively simple process, making taxonomic identification of the material, and comparison with adjacent Recent and other New Zealand Eocene faunas possible. These sponge body fossils and spicule microfossils indicate a fauna that was once dominated by hexactinellids, lithistid, and astrophorid demosponges. A qualitative comparison of the abundance and diversity of the Tutuiri Greensand sponge fauna with the present‐day Chatham Rise sponge fauna indicates that the late Paleocene‐early Eocene fauna is as diverse as the Recent fauna, for the hexactinellid sponges and astrophorid demosponges, and much more diverse for lithistid sponges. The paleoecology of the Tutuiri Greensand has been interpreted as inner to mid shelf water depths (50–250 m) but the poriferan fauna described here is more like that of the present‐day soft sediment benthic environment of the Chatham Rise at 800–1200 m.

Aquaculture trials of the New Zealand bath‐sponge Spongia ( Heterofibria ) manipulatus using lanterns - Michelle Kelly; Sean Handley; Mike Page; Paul Butterfield; Bruce Hartill; Shane Kelly (New Zealand Journal of Marine and Freshwater Research, 2004)
A submarine lantern system was trailed in the aquaculture of explants of the endemic New Zealand bath‐sponge Spongia ( Heterofibria ) manipulatus (Demospongiae: Dictyoceratida: Spongiidae) at four New Zealand sites, two in the Marlborough Sounds and two off Coromandel Peninsula. The main objectives were to compare growth rates of explants at different sites, compare these with those of control sponges, and to assess the utility of these lanterns for the culture of this species. After a period of 13 months, sponges at exposed Bonne Point in the Marlborough Sounds were on average 73% larger in estimated volume than at the start of the experiments. Growth rates of explants at exposed Port Charles, Coromandel, showed no significant change over the study period, although positive growth over spring 2003 was evident. Sponge explants at sheltered Wairangi Inlet and Kennedy Bay, in the Marlborough Sounds and Coromandel, respectively, did poorly, with most explants regressing in size and becoming moribund. Growth rates varied considerably between individuals at each location. Implications of the growth rate characteristics of S . ( H .) manipulatus , and the design and construction of the aquaculture lantern, for the future commercial production of this species are discussed.

Taxonomy of some halisarcida and homosclerophorida (Porifera: Demospongiae) from the indo‐pacific - Patricia R. Bergquist; Michelle Kelly (New Zealand Journal of Marine and Freshwater Research, 2004)
Several sponges with a thin encrusting form and of fragile construction have been collected in the Indo‐Pacific, and have proved difficult to differentiate, let alone identify, without recourse to electron microscopy. Here we re‐describe Halisarca melana de Laubenfels, 1954 from Palau, and H. metabola de Laubenfels, 1954 from Majuro Atoll in the Marshall Islands from new material, emphasising field characters such as coloration in life, surface features, and histological details accessible by light microscopy. Using similar characters two new species of Halisarca, H.ferreus sp. nov., from Zanzibar, Tanzania, and H . cerebrum sp. nov., from Palau, are recognised and described. Another genus belonging to a different subclass of Demospongiae also has fragile construction and encrusting growth form; this is Oscarella , and two new species of this genus are also described, O. stillans sp. nov. from the Philippines, and O. nigraviolacea sp. nov., from Pemba Island, Tanzania.

Systema Porifera: a guide to the classification of sponges. Edited by John N. A.Hooper and Rob W. M.vanSoest. Published in 2002 by Kluwer Academic/Plenum Publishers, Dordrecht, The Netherlands (http://www.wkap.nl). Hardbound set of two volumes, 1810 p. ISBN: 0–306–47260–0. Price: €625.00, £431.00, US$688.00 (email: kluwer@wkap.com (Americas); services@wkap.nl (elsewhere)). - Patricia R. Bergquist; Michelle Kelly (New Zealand Journal of Marine and Freshwater Research, 2004)

Non‐destructive video image analysis method for measuring growth in sponge farming: Preliminary results from the New Zealand bath‐sponge Spongia ( Heterofibria ) manipulatus - Sean Handley; Shane Kelly; Michelle Kelly (New Zealand Journal of Marine and Freshwater Research, 2003)
The skeleton of the New Zealand endemic sponge Spongia ( Heterofibria ) manipulatus (Demospongiae: Dictyoceratida: Spongiidae) has physical qualities that make it suitable for use as a bath‐sponge. The species is particularly abundant around exposed coastlines of D'Urville Island in the Marlborough Sounds and on the east coasts of Northland and Coromandel Peninsula. Growth rates and changes in the shape of explants of S . ( H .) manipulatus were monitored for a period of 12 months on a pilot marine farm near D'Urville Island, using digital video image analysis. This nondestructive method proved to be an accurate means of monitoring sponges for changes in size when compared with repeated wet‐weighing ex situ . Sponge explants increased in size by an average of 28.5% from September 2000 to June 2001, after which growth varied markedly to September 2001, with most of the explants changing little or shrinking in size. Implications of the biological and physical characteristics of S . ( H .) manipulatus , for the future commercial production of this species, are discussed.

The extracellular matrix protein ?IG-H3 is expressed at myotendinous junctions and supports muscle cell adhesion - Jill W. Ferguson; Brian S. Thoma; Michelle F. Mikesh; Randall H. Kramer; Kelly L. Bennett; Anthony Purchio; Bradford J. Bellard; Richard G. LeBaron (Cell and Tissue Research, 2003)

Revision of the sponge genus Pleroma Sollas (Lithistida: Megamorina: Pleromidae) from New Zealand and New Caledonia, and description of a new species - Michelle Kelly (New Zealand Journal of Marine and Freshwater Research, 2003)
Diagnostic morphological characters for the sponge genus Pleroma , relicts from a diverse group of lithistid sponges (Suborder Megamorina: Family Pleromidae) that were once common in the north‐western European late Jurassic to the late Cretaceous (c. 140–65 Ma), are reviewed following examination of new collections of known species from northern New Zealand and the south New Caledonian slope. Before this work, only two living species of Pleroma were known, the genus holotype P. turbinatum Sollas from Fiji, and P. menoui Lévi & Lévi from south New Caledonian seamounts. A new species, P. aotea n. sp., is described from northern New Zealand waters, extending the suite of diagnostic characters to include nodulose megaclone desmas and amphiaster microscleres. Megaclone desmas, indistinguishable from those of P. menoui and P. aotea n. sp., are recorded from the Oamaru Diatomite in southern New Zealand (late Eocene), and the Tutuiri Greensand, Chatham Island (late Palaeocene), respectively. These published and new microfossil discoveries establish a disjunct geographic distribution for Pleroma in New Zealand.

A recent sponge, Pleroma aotea Kelly (“Order” Lithistida: Family Pleromidae), in the late Eocene Ototara Limestone of Otago, New Zealand - Michelle Kelly; Daphne Lee; Shane Kelly; John S. Buckeridge (New Zealand Journal of Marine and Freshwater Research, 2003)
Numerous remarkably well‐preserved lithistid sponges recovered from the late Eocene‐early Oligocene Ototara Limestone at Kakanui, North Otago, represent the first sponge body fossils to be described from the New Zealand Cainozoic. The sponges are scattered throughout a 1–3‐m‐thick volcaniclastic limestone horizon immediately overlying the Kakanui Mineral Breccia. The fossils are now solid calcite, the former siliceous skeleton having been replaced during diagenesis. The Kakanui sponges are the only known body fossils remaining from an extremely diverse sponge fauna which formed a major component of the benthos in the Kakanui‐Oamaru region in late Eocene‐early Oligocene times (c. 35–33 Ma). The sponge body fossils are described and compared with living sponges that have a similar flattened globose morphology. The fossils are morphologically indistinguishable from the living lithistid sponge Pleroma aotea Kelly (“Order” Lithistida: Family Pleromidae) from deep‐water seamounts and banks off north‐eastern New Zealand, and are significant in that they represent a stratigraphic range for the species of more than 35 million years. The present‐day distribution of P. aotea , limited to silica‐rich deeper waters, is in marked contrast to the relatively shallow warm water volcanic environments occupied during the Palaeogene. This restriction, and that of related lithistid sponges to silica‐rich deeper waters off northern New Zealand, is paralleled in other demosponges and several calcareous invertebrate groups such as barnacles, bryozoans, and crinoids.

Assessing Vulnerability to Invasion by Nonnative Plant Species at Multiple Spatial Scales - THOMAS J. STOHLGREN; GENEVA W. CHONG; LISA D. SCHELL; KELLY A. RIMAR; YUKA OTSUKI; MICHELLE LEE; MOHAMMED A. KALKHAN; CYNTHIA A. VILLA (Environmental Management, 2002)

Riparian zones as havens for exotic plant species in the central grasslands - Thomas J. Stohlgren; Kelly A. Bull; Yuka Otsuki; Cynthia A. Villa; Michelle Lee (Plant Ecology, 1998)

Revision of Southwest Pacific Polymastiidae (Porifera: Demospongiae: Hadromerida) with descriptions of new species of Polymastia Bowerbank, Tylexocladus Topsent, and Acanthopolymastia gen. nov. from New Zealand and the Norfolk Ridge, New Caledonia - Michelle Kelly‐Borges; Patricia R. Bergquist (New Zealand Journal of Marine and Freshwater Research, 1997)
Specific diagnostic characters are reviewed and redefined for the genus Polymastia in northern New Zealand waters, to provide a framework for the recognition of new species, and for the revision and redefinition of other Polymastiidae. Eight new species of Polymastia are described, and Polymastia fusca Bergquist, P. hirsuta Berquist, and P. cf. massilis Carter are redescribed in the light of new material. Species of Polymastia which contain exotyles and centrotylote oxea in addition to the usual megasclere complement, provided the opportunity to redefine the polymastid genera Proteleia , and Tylexocladus , which would typically have been reserved respectively, for sponges with these spicules. Anew species of Tylexocladus is described from the Chatham Rise in southern New Zealand, providing a first record of the genus from this location. A new genus Acanthopolymastia is established for southern ocean Polymastiidae with acanthose centrotylote oxea, with Atergia acanthoxa Koltun from Antarctica as the type species. Two additional species from New Zealand and the Norfolk Ridge, New Caledonia are described, and all are compared to Atlantic species of the same genera. Suggestions for partitioning of shallow‐water Polymastia species are put forward.

Transcriptional regulation of the TGF-β2 gene in choriocarcinoma cells and breast carcinoma cells: Differential utilization of CIS-regulatory elements - Michelle Kingsley-Kallesen; Lance Johnson; Beáta Scholtz; David Kelly; Angie Rizzino (In Vitro Cellular & Developmental Biology - Animal, 1997)